LOVE AFFAIR REFLECTED AT HENRIK IBSENâS HEDDA GABLER PLAY (1890); AN INDIVIDUAL PSYCHOLOGICAL APPROACH - Primadani, Maya Berlian; Candraningrum, Dewi; Setyabudi, Titis (Universitas Muhammadiyah Surakarta, 2014)
The present study investigates love affair in Henrik Ibsenâs Hedda Gabler. This was library research of which primary data source was Hedda Gabler play supported by other resources such as the authorâs biography. The data were analyzed based on the individual psychology with a descriptive technique. The result showed that love affair was conducted by the major character, Hedda.